(untitled) (REMUNOM, 2026)
The expansion of digital technologies has significantly transformed social interactions, information production and the organization of personal assets, creating new challenges for contemporary inheritance law. In this context, digital assets have increasingly become part of individual patrimony, including social media accounts, cloud storage files, electronic communications and virtual assets with economic value. In light of this scenario, this study aims to analyze the legal challenges related to digital inventory within contemporary inheritance law, with particular attention to the protection of the privacy of the de cujus. The research is characterized as a narrative literature review, developed through the collection and examination of recent scientific publications addressing digital inheritance, succession of virtual assets and the legal implications arising from the digitalization of social relations. The findings indicate that the absence of specific regulation concerning the succession of digital assets generates legal uncertainty and interpretative conflicts among heirs, digital platforms and judicial authorities. Furthermore, the transmission of such assets involves not only patrimonial aspects but also issues related to privacy protection and personality rights of the deceased. It is concluded that the digital inventory represents a relevant instrument for the organization of virtual patrimony, contributing to greater legal certainty in succession processes and to the proper management of digital assets after the death of their holder.